Pengaruh Kebermaknaan Kerja Terhadap Loyalitas Kerja pada Karyawan Generasi Z di Kota Padang - Juniartika, Rifa; Utami, Sabrina Etika; Ihsani, Hanifa (Psyche 165 Journal, 2023)
The world's current employee population is dominated by the millennial generation and generation Z. The generation in question is a collection of people who categorize themselves according to their birth year, age, place of residence, and life events. Generation Z was born between 1995 and 2010 and grew up in the 2000s. Millennials are defined as those born between 1981 and 1994. The Generation Z is practical in the workplace and craves more safety and stability. Additionally, Generation Z tends to despise short-term jobs as well as lack long-term employment. Because of this, members of Generation Z are more likely to switch employers, which may have an impact on the business's profits and reputation. The purpose of this study was to examine the impact of meaningful work on Generation Z employees' commitment to their jobs. By distributing questionnaires online and setting restrictions on the types of respondents based on the Generation Z age range, a quantitative research methodology was applied. The findings demonstrated that work loyalty is greatly influenced by the meaning of the work. It was also discovered that up to 77% of respondents in generation Z said they preferred bosses who belonged to the millennial generation to those who belonged to generation X or the baby boomer generation. This demonstrates the need for superiors to pay attention to the aspirations of Generation Z if they want them to interpret their work and become devoted workers. Thus, it can be said that Generation Z employees are more loyal to their employers the more emphasis they place on their work.